The Influence of Social Media and Prices on Used Car Consumer Purchasing Decisions (Case Study at Ghiffari Motor Tangerang Showroom) - Ghiffari, Robby Yunsih Achmad; Yulizar, Ismayudin; Muljadi, Muljadi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to find out how price and social media influence consumers' decisions to buy used cars at the Ghiffari Motor Tangerang showroom. Social media promotion is now an important component of marketing strategies in the digital era. Price is still a consideration in determining which car to buy. This research aims to provide a significant perspective for automotive industry players so that they can improve their marketing tactics. In this research, a quantitative description method was used. The population studied consisted of thirty people randomly selected from September to November 2023 at the Ghiffari Motor used car showroom in Tangerang. A Likert scale was used in the online survey used to collect data for this investigation. SmartPLS is the analysis tool used. According to this research, price has an influence but is not statistically significant on the decision to purchase a used car with P (value) 0.178 > 0.050, however, social media has a fairly large influence with P (value) 0.002 < 0.050. With a proportion of 64.5%, price and social media have quite a large influence on purchasing decisions, while the remaining 35.5% is influenced by other factors not covered in this research.